2022
DOI: 10.3847/2041-8213/aca8a0
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Meteors Are Outliers in Material Strength

Abstract: The first interstellar meteor larger than dust was detected by US government sensors in 2014, identified as an interstellar object candidate in 2019, and confirmed by the Department of Defense in 2022. Here, we describe an additional interstellar object candidate in the CNEOS fireball catalog and compare the implied material strength of the two objects, referred to here as IM1 and IM2, respectively. IM1 and IM2 are ranked first and third in terms of material strength out of all 273 fireballs in the CNEOS catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This approach was delineated in [132, Section 3.1] for 1I/'Oumuamua, and is generalizable to nomadic worlds. On specifying 𝑅 ∼ 1000 km from earlier, we obtain 𝐷 ISO ∼ 1.3 × 10 4 AU from (3) and 𝐻 ≈ 1.6 after setting  ∼ 0.1 in (12). We also select a relative speed of ∼ 100 km/s based on previous sections (i.e., broadly the terminal velocity of the spacecraft), and adopt a worst-case fiducial positional uncertainty of 𝜃 var ∼ 10 −5 rad, which is commensurate with 1I/'Oumuamua [255,256], an ISO with unusual nongravitational acceleration.…”
Section: Constraints On the Flybymentioning
confidence: 81%
See 2 more Smart Citations
“…This approach was delineated in [132, Section 3.1] for 1I/'Oumuamua, and is generalizable to nomadic worlds. On specifying 𝑅 ∼ 1000 km from earlier, we obtain 𝐷 ISO ∼ 1.3 × 10 4 AU from (3) and 𝐻 ≈ 1.6 after setting  ∼ 0.1 in (12). We also select a relative speed of ∼ 100 km/s based on previous sections (i.e., broadly the terminal velocity of the spacecraft), and adopt a worst-case fiducial positional uncertainty of 𝜃 var ∼ 10 −5 rad, which is commensurate with 1I/'Oumuamua [255,256], an ISO with unusual nongravitational acceleration.…”
Section: Constraints On the Flybymentioning
confidence: 81%
“…Furthermore, electric sails and magnetic sails each have a well-defined upper limit corresponding to the typical speed of the solar/stellar wind, i.e., around 400 km/s, as higher spacecraft speeds would lead to a net deceleration instead. 12 Reviews of the magnetic and electric sail concepts can be found in [202] and [203].…”
Section: Electric Sails and Magnetic Sailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Below I demonstrate that if Dyson spheres existed to serve their civilizations for a limited time, most of them would have disintegrated within billions of years in the absence of extensive maintenance. In that case, their ejected fragments could appear as interstellar objects (Siraj & Loeb 2022a).…”
Section: Introductionmentioning
confidence: 99%